Refractory and progressively worsening nasal obstruction: case report of nasal osteoblastoma and literature review - Fang, Caishan; Wang, Ruizhi; Zhou, Min; Chen, Tengyu; Zhang, Qinxiu; Ruan, Yan; Li, Chunqiao (Frontiers in Oncology, 2023)
Nasal osteoblastoma (OB) is a rare and locally aggressive osteogenic tumor that has rarely been reported, and there is a lack of effective evidence data for its diagnosis and treatment. In this study, we report a 31-year-old female patient who presented with nasal congestion and associated progressive painless swelling of the left maxillofacial region. A preoperative computed tomography (CT) examination of the paranasal sinuses was performed, and based on the imaging presentation, the surgeon was unable to differentiate between OB, osteoid osteoma (OO), fibrous dysplasia of bone (FDB) and osteoblastic fibroma (OF). After excluding contraindications to surgery, the patient underwent nasal endoscopic excision of the left nasal mass, which was found to be gravel-like and difficult to remove cleanly during the operation. The mass was brittle and bled easily, resulting in inadequate exposure of the operative field, prolonged operation time, and substantial intraoperative blood loss. This indicates that definite preoperative diagnosis (biopsy of deeper parts of the mass is recommended) and appropriate preoperative preparations (e.g., preoperative angiography and embolization, adequate blood preparation) are very important. The intraoperative frozen and postoperative pathological results clearly identified the tumor as OB. No local recurrence of the tumor was observed at the 11-month postoperative follow-up.